Laboratory investigation into wettability alteration by different low salinity water compositions in sandstone rock - Shabib-Asl, A. (Society of Petroleum Engineers, 2015)
Low salinity water flooding is not an infant practice in petroleum industry; in fact, it has prevailed for several decades. Due to its significant contribution to the hydrocarbon recovery, the method has widely gained the attention of many researchers. From its early breakthrough, many studies have been conducted which have focused on comparative analysis between the low and high salinity water. Moreover, it has been verified that most of them were effective at brine concentration below 5000 ppm. With the purpose of enhancing oil recovery, low salinity water (LSW) with adequate composition and salinity is injected into the reservoir, which changes the wetting properties of the reservoir rock into those favoring oil recovery. However, the true mechanisms behind the process are still questionable and there is no specific optimum salinity range and type to be recommended. The present study investigates the wettability alteration on Berea sandstone rock with brine of different ion compositions and salinities. Measurements were performed on a set of 31 sandstone core slices primarily saturated with formation water and then aged in crude oil at 80Â° C and ambient pressure. All slices were removed from oil and aged with different low salinity water and formation brine at same conditions. The low salinity water consisted of 30 samples of different compositions with concentrations ranging from 500 to 6500 ppm. The formation water contained high concentration of magnesium and calcium divalent ions (i.e., Mg+2 and Ca+2) at 130,000ppm. The examination of wettability alteration was performed by using the sessile drop method at specified ranges of time. The results revealed that significant change in wettability was observed with the low salinity water composition of potassium and sodium monovalent ions (i.e., K+ and Na+) as compared to the divalent cations of Mg+2 and Ca+2. Copyright 2015, Society of Petroleum Engineers.